PENATALAKSANAAN PENYAKIT KUSTA DENGAN KECACATAN DERAJAT II PADA LAKI LAKI USIA 42 TAHUN MELALUI PENDEKATAN DOKTER KELUARGA - Rizky Arif Prasetyo; Fitria Saftarina (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2019)
Introduction: Leprosy is a chronic infectious disease caused by obligate intracellular Mycobacterium leprae bacteria. Bacteria attack peripheral nerves as the first affinity. This leprosy causes a very complex problem, not only from a medical point of view, but extendsto social, economic and cultural problems. This is because if leprosy is not diagnosed and treated comprehensively, it can result in permanent disability in the sufferer. Case Illustration: A 42-year-old man with a major complaint of red spots accompanied by numbness in the hands and feet, fingers of the left hand is difficult to move, body weight drops dramatically, and the entire body feels painful.Physical examination: The left antebrachii region and the left pedis region are obtained from the erythomatous macula to hypopigmentation, multiple, firm borders, placard size, squamous (+), atrophy (+), anesthesia (+). Feeling sensibility, pain, temperature in the lesion area is reduced. Peripheral nerve palpation is painful and thick in the left ulnar nerve,N. left lateral Proneus and N. left posterior tibialis. Chewy consistency in all nerves with palpation examination.Supporting Examination: Ziehl Nielsen staining is found AFB (+) Solid (+) Fragmental (+) Globi (+) Granule (-)Management: Education and counseling regarding supervisors taking medication, explaining the diseases experienced by patients as well as introducing, preventing and interfering with disability. Interventions that are carried out are divided into patient centers (non-medical and psychiatric), family focus and community oriented.Discussion: There have been three cardinal signs of leprosy in patients as a basis for diagnosing leprosy. Patient are classified as second degree disability based on WHO disability rates.